2018
DOI: 10.1155/2018/8952646
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkaloid Extract from African Jointfir (Gnetum africanum) Leaves on Manganese‐Induced Toxicity in Drosophila melanogaster

Abstract: Metal-induced toxicity in fruit fly (Drosophila melanogaster) is one of the established models for studying neurotoxicity and neurodegenerative diseases. Phytochemicals, especially alkaloids, have been reported to exhibit neuroprotection. Here, we assessed the protective effect of alkaloid extract from African Jointfir (Gnetum africanum) leaf on manganese- (Mn-) induced toxicity in wild type fruit fly. Flies were exposed to 10 mM Mn, the alkaloid extract and cotreatment of Mn plus extract, respectively. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 67 publications
3
6
0
Order By: Relevance
“…Apart from producing immune response, cell proliferation and differentiation, NO is also being reported as a proinflammatory mediator [33] . And according to the study, the alkaloid extract of African Jointfir is able to ameliorate the elevated level of NO which suggests its anti-inflammatory property [30] . So in this way, this extract can be an innovative candidate for the isolation purpose obtaining possibly a novel or known compound which is active in treating neurodegeneration.…”
Section: ~ 416 ~mentioning
confidence: 92%
See 1 more Smart Citation
“…Apart from producing immune response, cell proliferation and differentiation, NO is also being reported as a proinflammatory mediator [33] . And according to the study, the alkaloid extract of African Jointfir is able to ameliorate the elevated level of NO which suggests its anti-inflammatory property [30] . So in this way, this extract can be an innovative candidate for the isolation purpose obtaining possibly a novel or known compound which is active in treating neurodegeneration.…”
Section: ~ 416 ~mentioning
confidence: 92%
“…Therefore, the moiety which can ameliorate such free radicals will be very beneficial in order to treat various neurodegeneration. And the alkaloid extract of African jointfir is found to be able to decrease such elevated free radicals and besides, it is also reported to inhibit the acetylcholine esterase enzyme in the in vitro study of fruitfly model [30] . It produces a conception to employ this extract to treat neurodegenerative disease such as AD and dementia because inhibiting acetylcholine esterase enzyme will lead to increase the life span of acetyl choline which is responsible for the cognitive ability, memory/learning, motor function and locomotion [31] .…”
Section: ~ 416 ~mentioning
confidence: 98%
“…In addition, the extract may reduce epithelial cell death and reactive oxygen species (ROS) levels, thereby improving intestinal morphology [ 53 ]. Using adult wild-type Drosophila , Oboh et al (2018) showed that Gnetum africanum extract inhibited Mn-induced elevation of NO and ROS levels [ 54 ]. To screen the protective effects of selected traditional plants on intestinal cells, Zhou et al (2016) utilized adult wild-type Drosophila fed with toxic compounds.…”
Section: Examples Of Studies To Test the Immunomodulatory Effect Of P...mentioning
confidence: 99%
“…The protective properties of an alkaloid extract from African Jointfir (Gnetum africanum) leaf against Mn toxicity was also tested in D. melanogaster as a model. The extract counteracted Mn-induced increase in acetylcholinesterase enzyme (AChE) activity, nitric oxide (NO), and ROS levels [149].…”
Section: Natural Compoundsmentioning
confidence: 99%
“…Popular name: African jointfir Family: Gnetaceae Alkaloids [149] Reestablished acetylcholinesterase (AChE) activity Reduced nitric oxide (NO), and reactive oxygen species (ROS) levels [149] Drosophila melanogaster Basella alba L.…”
Section: Echium Amoenum Fisch and Ca Meymentioning
confidence: 99%